Tuhost valivých ložisek - Krišpín, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Předložená bakalářská práce se zabývá tuhostí modelové konfigurace hřídele uložené letmo ve dvou jednořadých radiálních kuličkových ložiscích. V úvodu se práce věnuje valivým ložiskům a parametrům ovlivňující jejich tuhost. Poté je navržena modelová sestava a proveden výpočet její tuhosti v softwaru MESYS. Dále je na této sestavě provedeno experimentální měření tuhosti, která se zjišťuje měřením deformace hřídele při daném zatížení. Hodnoty jsou vzájemně porovnány a jsou určena citlivá místa ve výpočtu. Výsledky práce vedou zejména k určení velikosti vlivu jednotlivých parametrů na změnu tuhosti a ověření funkčnosti softwaru MESYS.

Given bachelor thesis deals with stiffness of model shaft configuration which is mounted overhung in two single row radial ball bearings. Initial part of the thesis is focused on roller bearings and parameters affecting their stiffness. Then a model assembly is designed. The stiffness calculation calculation of the assembly is performed by MESYS software. Subsequently, an experimental stiffness measurement is performed. Stiffness is determined by measuring the deformation of the shaft at given load. Values are compared with each other and the sensitive points in the calculation are determined. The results of the thesis mainly lead to determination of the magnitude of the influence of individual parameters on the change in stiffness. The functionality of the MESYS software was verified.
Rolling bearing stiffness
Keywords: tuhost; valivé ložisko; software MESYS; stiffness; roller bearing; software MESYS